2016
DOI: 10.1002/ange.201511999
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Tight and Selective Binding of a Medicinal Dicarbene Gold(I) Complex to a Telomeric DNA G‐Quadruplex: a Joint ESI MS and XRD Investigation

Abstract: The dicarbene gold(I) complex [Au(9-methylcaffein-8-ylidene) 2 ]BF 4 is an exceptional organometallic compound of profound interest as ap rospective anticancer agent. This gold(I) complex was previously reported to be highly cytotoxic toward various cancer cell lines in vitro and behaves as aselective G-quadruplex stabilizer.Interactions of the gold complex with various telomeric DNAm odels have been analyzed by ac ombined ESI MS and X-ray diffraction (XRD) approach.ESI MS measurements confirmed formation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…It was already confirmed that [(NHC) 2 Au I ] + complexes show significantly improved inhibition of cancer cell proliferation compared to the respective (NHC)Au I X complexes. 7 , 9 , 12 , 17 , 46 49 …”
Section: Introductionmentioning
confidence: 99%
“…It was already confirmed that [(NHC) 2 Au I ] + complexes show significantly improved inhibition of cancer cell proliferation compared to the respective (NHC)Au I X complexes. 7 , 9 , 12 , 17 , 46 49 …”
Section: Introductionmentioning
confidence: 99%
“…[11,12,17,18] Thisp henomenon can also be explained by the stabilityo ft he complexes. More recently,a lternative targets have been identified for gold(I) NHC complexes, namely telomeric DNA G-quadruplexes [19] and zinc finger proteins such as poly(adenosine diphosphate-ribose) polymerase 1( PARP-1), [20] As tructurally diverse library of 14 gold(I)c ationic bis(NHC)a nd neutralm ono(NHC)c omplexes (NHC: N-heterocyclic carbene) was synthesized andc haracterized in this work. Four of them were new cationic gold(I) complexes containing functionalized NHCs, and their X-ray crystal structures are presented herein.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of these compounds against platinum complexes is that they differ in their mechanism of action. Whereas platinum compounds interact with nucleic acids, gold-containing drugs display a higher variety of targets, including non-canonical DNA structures [9,10], zinc finger proteins [11] or the redox enzyme thioredoxin reductase (TrxR). Gold complexes are able to inhibit TrxR via interacting with the selenium atom [12] of the selenocysteine moiety.…”
Section: Introductionmentioning
confidence: 99%